Bibliometric Analysis of Research Trends on Food Taboos during Pregnancy in a Socio-Cultural Context - Susanti, Sri; Sukmana, Oman; Susilo, Rahmad K. Dwi (Inspirasi Foundation, 2025)
Introduction: Food taboos during pregnancy are common cultural practices in many developing countries. While intended to protect maternal and fetal health, these taboos often contradict recommended nutritional guidelines and may contribute to maternal undernutrition. Objective: This study aims to analyze global research trends on food taboos among pregnant women using a bibliometric approach to identify knowledge gaps and emerging themes. Method: A bibliometric analysis was conducted using data retrieved from the Scopus database covering publications from 2000 to 2024. The data were analyzed using VOSviewer software to map publication patterns, keyword co-occurrence, and thematic clusters. Results: A total of 55 relevant articles were identified. The number of publications began to increase significantly in 2013, peaking in 2019. Most research originated from developing countries, notably Ethiopia and Nigeria, with a disciplinary focus on medicine, agricultural and biological sciences, nursing, and social sciences. The bibliometric mapping identified three main thematic clusters: (1) food taboos and dietary preferences, (2) health knowledge and attitudes, and (3) maternal nutritional status linked to socioeconomic factors. Emerging keywords included nutrition, anemia, diet, and undernutrition. However, key issues such as socioeconomic dimensions and dietary diversity remain underexplored. Conclusion: Research on food taboos in pregnancy is growing but remains geographically and thematically concentrated. Future studies should adopt interdisciplinary and culturally sensitive approaches to address the nutritional implications of food taboos during pregnancy. These findings provide valuable insights for policymakers and researchers in designing effective maternal health interventions.